Impact of serum bilirubin levels and preoperative biliary drainage on perioperative complications of pancreaticoduodenectomy - Li, Yilan; Pu, Sicheng; Zong, Kezhen; Liao, Rui; Huang, Zuotian; Huang, Jianbo; Liu, Yawen; Zhou, Baoyong; Wu, Zhongjun (Frontiers in Medicine, 2025)
BackgroundThe effect of elevated preoperative serum bilirubin on complications after pancreaticoduodenectomy (PD) remains uncertain. Preoperative biliary drainage (PBD) effectively reduces serum bilirubin values; however, its impact on PD complications remains debatable.MethodsWe conducted a retrospective analysis on patients who underwent PD at the First Affiliated Hospital of Chongqing Medical University from October 2018 to July 2023. Patients were categorized into quartiles based on preoperative serum bilirubin levels. Multivariable logistic regression was used to investigate the relationship between bilirubin and the risk of PD complications. Restricted cubic spline (RCS) analysis was conducted to assess the dose–response relationship between bilirubin levels and PD complications. Furthermore, a 3-way interaction of PD complications, preoperative serum bilirubin, and PBD was examined.ResultsA total of 326 patients participated in the study. Multivariate logistic regression analysis revealed that higher preoperative serum bilirubin levels increased the likelihood of perioperative PD complications. RCS analysis revealed a significant linear dose–response relationship between bilirubin levels and the risk of PD complications. While PBD did not independently affect PD complications, there was a significant 3-way interaction of PD complications, preoperative serum bilirubin levels, and PBD, indicating that patients with serum bilirubin values exceeding 10 times the upper limit of normal (≥ 171 μmol/L) exhibited a lower risk of complications through PBD.ConclusionElevated preoperative serum bilirubin increases the risk of complications after PD. Patients with high preoperative serum bilirubin values (≥ 171 μmol/L) undergoing PD benefit from PBD.